The Correlation among AI-Assisted English Learning, Technology Acceptance, and Willingness to Use English among English Education Alumni Graduates from UIN Raden Mas Said Surakarta - Adam Ghivari; Sujito (PT. Hasba Edukasi Mandiri, 2025)
This quantitative correlational study was conducted to find out the relationship between AI-Assisted English Learning, Tech Acceptance, and Willingness to Use English in the AI Learning, with the target population being the graduates of the English Language Education program at UIN Raden Mas Said Surakarta. There were 30 respondents taken for this quantitative correlation analysis, with the respondents completing an online questionnaire designed in relation to the AI usage scale, Tech Acceptance Model, and Willingness to Communicate. The data revealed that both predictors were found to be at high levels, denoting the involvement of the graduates in learning English and their positive attitude towards technology. AI-supported learning in English was revealed to be positively significant with Willingness to Use English (ρ =.386, p =.035), indicating that regular use of AI technologies boosts alumni confidence and drive when speaking English. In contrast, Willingness to Use English did not significantly correlate with Technology Acceptance (ρ =.155, p =.414). Nonetheless, the combination of the two variables explained 23.2% of the variance (R² =.232) and significantly contributed to the variation in Willingness to Use English (F = 4.085, p =.028). This result implied that the integration of AI with English language learning could enhance the quality of graduates’ communication preparedness, especially when they possessed an optimistic attitude towards technology. Future studies involving more factors, such as affective elements, should be conducted to further explore English language usage behavior post-graduation.